2016
DOI: 10.1073/pnas.1607289113
|View full text |Cite
|
Sign up to set email alerts
|

Human cortical–hippocampal dialogue in wake and slow-wave sleep

Abstract: Declarative memory consolidation is hypothesized to require a twostage, reciprocal cortical-hippocampal dialogue. According to this model, higher frequency signals convey information from the cortex to hippocampus during wakefulness, but in the reverse direction during slow-wave sleep (SWS). Conversely, lower-frequency activity propagates from the information "receiver" to the "sender" to coordinate the timing of information transfer. Reversal of sender/ receiver roles across wake and SWS implies that higher-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 62 publications
(87 reference statements)
7
85
0
Order By: Relevance
“…Hippocampal-cortical activity is state dependent, so the light anesthesia used here may alter their characteristics (34,66,67,79). Nevertheless, prior work revealed synchronized interhemispheric delta oscillations as a major contributor to infraslow rsfMRI connectivity in anesthetized rodents (16,17).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Hippocampal-cortical activity is state dependent, so the light anesthesia used here may alter their characteristics (34,66,67,79). Nevertheless, prior work revealed synchronized interhemispheric delta oscillations as a major contributor to infraslow rsfMRI connectivity in anesthetized rodents (16,17).…”
Section: Discussionmentioning
confidence: 91%
“…Note that a recent human rsfMRI study of low-frequency hippocampal-cortical propagation also showed characteristics of activity propagation between the hippocampus and visual cortex (34). Interestingly, the robust detection of BOLD responses in bilateral visual cortices observed in the present study suggests that low-frequency activity initiated in dDG may drive slow oscillatory activity to coordinate visual memory replay in the visual cortex and hippocampus (C) Quantification of the interhemispheric rsfMRI connectivity (Left; n = 12; paired t test followed by Bonferroni's post hoc test; *P < 0.05, **P < 0.01, and ***P < 0.001; error bars indicate ±SEM).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Resting state fMRI measures something very different; since there is no imposed task, RS-fMRI reveals resting state networks, that is, the topography of temporally synchronous spontaneous neural activity. Although the physiological functions of intrinsic brain activity remain uncertain (for discussion see 44,45 ), RSNs are of practical interest as they topographically resemble fMRI responses to a wide range of cognitive, sensory, and motor tasks. Here, we compare T-fMRI responses to a finger-tapping task, which recruits the hand area of sensori-motor cortex, versus the full sensorimotor network as revealed by RS-fMRI, which is more extensive and includes Brodmann areas 1–4 as well as supplementary motor cortex.…”
Section: Discussionmentioning
confidence: 99%